2010
DOI: 10.1007/s12289-010-0996-5
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced Lemaitre model formulation for materials processing damage computation

Abstract: ABSTRACT:The Lemaitre damage model is now widely used to deal with coupled damage analyses for various mechanical applications. In this article, different extensions of the model are presented and discussed to deal with complex multiaxial configurations -such as multi-stages bulk forming processes. A specific treatment is done to account for compressive damage growth, and a stress triaxiality cut-off value is considered to avoid any damage evolution below a critical negative triaxiality. The damage potential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…The Lemaitre model has been successfully applied to predict fracture in several forming processes at high stress triaxiality (e.g. Bouchard et al, 2011) while the B&W model has been shown to be capable of predicting fracture for different mechanical tests at different loading configurations involving pure shear (see Cao et al, 2013b). To the present authors knowledge, this is the first time that the B&W model is used to predict fracture in multi-stages wire drawing and rolling processes.…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lemaitre model has been successfully applied to predict fracture in several forming processes at high stress triaxiality (e.g. Bouchard et al, 2011) while the B&W model has been shown to be capable of predicting fracture for different mechanical tests at different loading configurations involving pure shear (see Cao et al, 2013b). To the present authors knowledge, this is the first time that the B&W model is used to predict fracture in multi-stages wire drawing and rolling processes.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Moreover, based on the observations of Bridgman experimental results (Bridgman, 1952), Bao and Wierzbicki (2005) showed that there exists a limit of the stress triaxiality (Á) below which, there is no damage. This observation has been applied to the Lemaitre model and implemented in Forge ® by Bouchard et al (2011). The damage evolution is therefore modified as:…”
Section: The Lemaitre Damage Modelmentioning
confidence: 99%
“…Various tests were performed for the identification and analysis of significant damage and failure mechanisms typical for cold bulk forming processes. One of these tests is a compression of a cylindrical billet with a longitudinal notch [1]. This geometry is interesting for two main reasons: fracture is easily localized since it appears at the center of the notch as the notch opens both in the radial and longitudinal directions during the longitudinal compression; mechanical loadings are close to what the material experiences during bulk forming processes.…”
Section: Experiments and Simulationsmentioning
confidence: 99%
“…Such forming operation includes forward, backward, and combined forward-backward extrusion. The forming defects with the forward or backward extrusion processes, such as Chevron cracks, have been investigated extensively [1][2][3][4][5][6]. However, the investigations on the forming defects with combination extrusion, such as piercing or surface-crack defects, are still scarce.…”
Section: Introductionmentioning
confidence: 99%